Effects of acute smoking on brain activity vary with abstinence in smokers performing the N-Back Task: a preliminary study - Xu, Jiansong (2006)
We previously reported that compared with a non-deprivation state, overnight abstinence from cigarette smoking was associated with higher brain activity in the left dorsolateral prefrontal cortex (L-DLPFC) during a low demanding working memory challenge, and little increase beyond this activity level during more taxing working memory conditions. In the present study, we aimed to assess how recent smoking (overnight abstinence Vs smoking ad libitum) influenced the effect of smoking a cigarette on brain activity related to a working memory challenge. Six smokers performed the N-Back working memory task during functional magnetic resonance imaging (fMRI) both before and after smoking a cigarette in each of two test sessions: one following overnight abstinence from smoking (>13 h) and the other following ad libitum smoking. Task-related activity in L-DLPFC showed a significant interaction between the effects of acute smoking, test session, and task load. After overnight abstinence, post-smoking brain activity in L-DLPFC was lower than before smoking at low task-load and higher at high task-load; corresponding activity on a day of ad libitum smoking was higher at low load and lower at high task-load after smoking during the session. These data suggest that the effect of acute smoking on working-memory processing depends on recent prior smoking and task-load. In particular, they provide preliminary evidence that functional efficiency of working memory is improved by smoking a cigarette during abstinence, while the effect of a cigarette in a non-deprived state varies with the nature and difficulty of the working memory challenge. This interaction merits further examination in larger studies specifically designed to consider this issue.